Analisis Pengaruh Purifikasi Oli Transformator terhadap Tegangan Tembus Oli Tranformator - I Gede Loucian Cass Tanjung; I Wayan Dikse Pancane (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
This study aims to analyze the effect of transformer oil purification on oil breakdown voltage and evaluate its benefits in maintaining transformer performance and reliability. Oil purification is a crucial preventive maintenance step to preserve insulation quality and prevent operational failures caused by reduced dielectric properties. The study was conducted through several stages, including data collection, oil purification, measurement of breakdown voltage before and after purification, and evaluation of results. Data collection involved measuring the oil’s electrical properties according to SPLN 49-1:1982 and observing results using a Break Down Voltage (BDV) test. Purification of a Trafindo 400 kVA transformer was performed through visual inspection, connecting the inlet and outlet hoses to the purification machine, and circulating the oil until the breakdown voltage met the required standards. Results indicated that the oil breakdown voltage before purification was below standard due to reduced insulation quality caused by water contamination, charcoal particles, thermal degradation, and dissolved gases that weakened dielectric properties. Additional factors such as electrical stress, mechanical stress, and excessive loading also contributed to insulation deterioration. After purification, the oil breakdown voltage increased significantly to meet the standard of >30 kV/2.5 mm, demonstrating that purification effectively restores the oil’s insulating capacity and supports optimal transformer performance. Analysis confirms that the transformer oil remains suitable for use, and routine annual purification is recommended to maintain reliability, efficiency, and operational performance. This study highlights oil purification as an effective preventive measure for transformer stability, extending operational life, and reducing the risk of insulation failure. The findings provide valuable guidance for transformer maintenance in the electricity industry, ensuring safe and optimal long-term operation.